Murders of a feather - Brady, Eileen (Veterinarian) (Brady, Eileen (Veterinarian). Kate Turner, D.V.M. mystery., 2023)
"It's February in the Hudson Valley and Oak Falls veterinarian Dr. Kate is once again up to her galoshes in corpses Hudson Valley winters can be brutal...and deadly! Dr. Kate is once again on the case (not to mention thin ice) after discovering a young engaged couple frozen to death in the lake. To make matters worse, her temporary receptionist appears to have overdosed from a recreational sedative used at the animal hospital. Kate barely has time to dread Valentine's Day (and the fact that she's alone on this holiday, once again) as the police investigation shows that all three fatalities are in fact homicides. But who would want the young couple dead, just as they were embarking on a new life together? And who pumped the temp employee full of enough animal tranquilizers to drop an ox? Kate doesn't know where to begin until she stumbles upon a connection between the three victims and decides she needs to investigate further. But will her investigation leave her any time to get to know the handsome large animal vet she's just met on a house call? And is the injured wild crow she's taken under her wing in fact an omen of more bad things to come?"--